An advertising media: the relationship of advertising message, image and language usage towards sensitivity in Islamic perspective / Norazlinda Mohammad … [et al.] - Mohammad, Norazlinda (2015)
As the world is becoming more unwrap and increasingly globalized, the portrayal of certain products and services in advertising media has inflict the sensitivity of the main religion in Malaysia to be touched. This issue has evokes dissatisfaction in society and indirectly affects the credibility of the advertisers. Print advertisement is an interesting issue to be discussed on especially in the perspective of promoting the healthcare products and services towards Muslim society in Malaysia. This research paper attempts to study on the elements in offensive print advertisements and the unethical advertising appeals being used in printed media in Malaysia that can violate Muslims’ sensitivity. This study uses quantitative approach in which 100 student in Universiti Teknologi MARA (UiTM) Melaka will be randomly selected as the sample to participate in the self-administered questionnaires. The expected findings will indicate that those with high religious belief differ in terms of their level of offensiveness towards print advertisements from those of lower level of religiosity. Therefore, the advertising media should be concerned in any elements that could jeopardize their ethicality in producing print advertisements and prioritize the sensitivity off all religions in Malaysia.